Íons terras raras inseridos em matrizes poliméricas de germânio e enxofre para preparação de materiais com propriedades ópticas - Salvi, Denise Toledo Bonemer De [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work presents the study of the flexible and transparent polymeric materials based on germanium sulfide, obtained using GeCl4 and 1,3-propanedithiol as precursors. Also presented are the properties of luminescence related to the inclusion of rare earth ions Er3+, targeting applications such as matrix for luminescent materials. The materials were characterized through the following techniques: UV-VIS, SEM, XRD, FTIR, Raman scattering, 1H and 13C NMR, TG / FTIR, DSC, luminescence and BET. These materials have transparency in the UV-VIS spectral region (about 70%), %), thermal stability up to 200°C and glass transition located at temperatures below 0°C (-37°C, -56°C and -45°C) as shown by DSC curves. SEM images showed that the polymer is homogeneous and presents formation of crystals in some regions of the surface These polymers also exhibit Ge-S bonds in its structure, as can be observed through FTIR (bands at 399, 401, 432 and 470 cm-1) and Raman (peaks at 361 and 430 cm-1) spectroscopies, and the diffraction patterns X-rays, which suggest the formation of a mixture of GeS2 and GeO2 phases (also confirmed through EDS analysis). 1H and 13C NMR measurements provided information related to the reaction between 1,3-propanedithiol and GeCl4, and also in relation to the structure of Geprop materials. The coupled TGA-FTIR technique was used to investigate the degradation of the sample. The luminescence results suggest future applications of Geprop samples as matrices for obtaining luminescent materials. BET analysis indicates that these materials have no pores (as also observed in SEM images). Taken together, the results suggest that these materials are good candidates for optical applications, besides the possibility of use at low temperatures.

Este trabalho apresenta o estudo dos materiais poliméricos flexíveis e transparentes baseados em sulfeto de germânio, obtidos utilizando-se GeCl4 e 1,3- propanoditiol como precursores. São apresentadas também as propriedades de luminescência relacionadas à inserção de íons terras raras Er3+, visando aplicações como matrizes para materiais luminescentes. Os materiais obtidos foram caracterizados através das seguintes técnicas: UV-Vís, MEV, DRX, FTIR, espalhamento Raman, RMN de 1H e 13C, TG/FT-IR, DSC, Luminescência e BET. Estes materiais apresentam transparência na região espectral UV-Vís (em torno de 70%), estabilidade térmica até 200°C e transição vítrea localizada em temperaturas abaixo de 0°C (-37°C, -56°C e -45°C), como mostrado pelas curvas DSC. Imagens de MEV mostraram que o polímero é homogêneo e apresenta formação de cristais em algumas regiões da superfície. Estes polímeros apresentam também ligações Ge-S em sua estrutura, como pode ser observado através das espectroscopias FTIR (bandas em 399, 401, 432 e 470 cm-1) e Raman (picos 361 e 430 cm-1), e dos difratogramas de raios-X, que sugerem a formação de uma mistura de fases de GeS2 e GeO2 (confirmado também pela análise de EDS). As medidas de RMN de 1H e 13C permitiram obter informações em relação à reação entre 1,3-propanoditiol e GeCl4, e também em relação à estrutura dos materiais Geprop. A técnica acoplada TGA-FTIR foi utilizada para investigar a degradação da amostra. Os resultados de luminescência sugerem futuras aplicações das amostras Geprop como matrizes para obtenção de materiais luminescentes. A análise BET aponta que estes materiais não apresentam poros (como também observado nas imagens de MEV). Reunidos, os resultados sugerem que estes materiais são bons candidatos para aplicações óticas, além de possibilidade de utilização em baixas temperaturas.
Keywords: Germanio; Polímeros; Érbio; Sulfetos; Terras raras; Germanium